Speciation of U, Se, As and Sr in Makook Karstic water system, Kurdistan Region, Iraq - Mustafa, Omed Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2016)
Speciation of trace elements in water system is essential for understanding of the mobility, toxicity, bioavailability and transport characteristics of these elements. This study presents an evaluation of different factors affecting speciation of uranium (U), selenium (Se), arsenic (As) and strontium (Sr) in Makook Karstic water system. Results show a temporal variability of U, Se, As and Sr species within the different karst aquifers. The abundant species are U(VI), U(IV), Se(IV), Se(VI), As(V), As(III), Sr2+ and SrHCO3+. It is observed that these species are significantly controlled by pH, redox (pE), temperature (T), dissolved organic carbon (DOC), dissolution of calcite and dolomite minerals and variation of springs discharge. Mineralogical content of the host rocks controls the speciation of the studied elements as well. Therefore, different aquifers show different speciation responses for the same element. This study illustrates the speciation mechanism in karstic waters.
Keywords: Karstic water,Speciation; Makooksystem; DOC,Kurdistan Region